2017
DOI: 10.1007/978-3-319-46503-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the Stressosome Signalling Hub

Abstract: The stressosome is a multi-protein signal integration and transduction hub found in a wide range of bacterial species. The role that the stressosome plays in regulating the transcription of genes involved in the general stress response has been studied most extensively in the Gram-positive model organism Bacillus subtilis. The stressosome receives and relays the signal(s) that initiate a complex phosphorylation-dependent partner switching cascade, resulting in the activation of the alternative sigma factor σ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 100 publications
0
61
0
Order By: Relevance
“…Motivations for a similar adaptation of B. subtilis are three-fold. First, the topic of cell stress is a significant research front, in which B. subtilis is a commonly used system (Pane-Farre et al, 2017). Second, a B. subtilis strain adapted to high-temperature growth could have practical value for biotechnological applications, potentially reducing energy use and lowering production costs for fermentation, as has been noted for thermophilic platforms (Taylor et al, 2011).…”
Section: Evolution With Selection For High-temperature Growthmentioning
confidence: 99%
“…Motivations for a similar adaptation of B. subtilis are three-fold. First, the topic of cell stress is a significant research front, in which B. subtilis is a commonly used system (Pane-Farre et al, 2017). Second, a B. subtilis strain adapted to high-temperature growth could have practical value for biotechnological applications, potentially reducing energy use and lowering production costs for fermentation, as has been noted for thermophilic platforms (Taylor et al, 2011).…”
Section: Evolution With Selection For High-temperature Growthmentioning
confidence: 99%
“…Activation of SigB relies on transduction of intestinal signals by bacterial envelope components, such as the membrane miniprotein Prli42, discovered recently through mass spectrometry (MS)‐based proteomics, and a cytoplasmic complex composed of multiple copies of the three proteins RsbR, RsbS and RsbT, the stessosome (Impens et al, ). Studies in Bacillus subtilis showed that the RsbS scaffold protein and RsbR form the core of the stressosome, which is phosphorylated by RsbT upon stress (Pané‐Farré et al, ). Atomic resolution cryo‐electron microscopy (EM) of the RsbR‐RsbS core in Listeria revealed a similar 60‐mers icosahedron organisation and its potential activation by phosphorylation of RsbR (Figure ), providing a refined model of stressosome mechanics and signal transduction, that may extend to other bacteria (Williams et al, ).…”
Section: Listeria Transition From the Environment To The Mammalian Hostmentioning
confidence: 99%
“…Studies in Bacillus subtilis showed that the RsbS scaffold protein and RsbR form the core of the stressosome, which is phosphorylated by RsbT upon stress (Pané-Farré et al, 2017). Atomic resolution cryoelectron microscopy (EM) of the RsbR-RsbS core in Listeria revealed a similar 60-mers icosahedron organisation and its potential activation F I G U R E 1 Schematic representation of Listeria monocytogenes infection cycle in host cells.…”
mentioning
confidence: 99%
“…Three major functions are linked to this situation: overcoming deleterious actions of non‐living and living organisms, escaping to other niches, possibly far away or staying in place. Bacillus subtilis monitors this situation via specific sigma factors (Helmann, 2016) and protein phosphorylation cascades (Schultz, 2016; Pane‐Farre et al ., 2017). These will not be further discussed here (except to note that the concept of stress being very ambiguous, as all living organisms suffer multiple transitions, it should probably be avoided to be replaced by the idea of transition management).…”
Section: Bacillus Subtilis Exploring Its Environmentmentioning
confidence: 99%